Field Journals of Henry A. Pilsbry Pertaining to Arizona - Henry A. Pilsbry; Joseph C. Bequaert; Walter B. Miller (Hello World!, 1972)
The notes compiled here have been extracted from the field journals of Henry A. Pilsbry. The journals are on file in the Department of Mollusks, Academy of Natural Sciences of Philadelphia. We thank Dr. Robert Robertson and Mrs. Nancy Rulon for making the journals available and for other assistance.